Comprehensive landscape and oncogenic role of extrachromosomal circular DNA in malignant biliary strictures - Zhuo Cheng; Xuanmei Luo; Wenzheng Liu; Xiaofang Lu; Hong Chang; Yingchun Wang; Wei Zheng; Xiue Yan; Yonghui Huang (Cell & Bioscience)
Abstract Background Extrachromosomal circular DNA (eccDNA) is crucial for carcinogenesis and bile has direct contact with malignant biliary strictures, yet eccDNA features in bile and its function in malignant biliary strictures remain underexplored. Results We observed the widespread presence of eccDNA in bile and systematically profiled the landscape of bile cell-free eccDNA (bcf-eccDNA). For functional exploration, a simple and efficient workflow was designed to synthesize large eccDNA particularly containing multiple regions. Compared with the noncancer group, bcf-eccDNAs in the cancer group had different origins and larger sizes with six characteristic peaks. These peaks were also identified in the validation cohort (100%). There were more bcf-eccDNA carrying LINC00598 or CELF2 in malignant biliary strictures, showing potential diagnostic performance in training and validation cohorts (all AUCs > 0.9). Bcf-eccDNAs carried cancer-related mutations, which could guide treatment. EccDNA carrying miR-106a/363 cluster or miR-374b/421 cluster were proven to regulate cancer gene expression, accelerate tumor proliferation, and inhibit tumor apoptosis. Conclusions This study profiles a comprehensive bcf-eccDNA landscape in patients with biliary strictures and offers valuable insights into eccDNA's role in bile liquid biopsy and carcinogenesis.